2012
DOI: 10.1089/ten.tea.2011.0225
|View full text |Cite
|
Sign up to set email alerts
|

Functional Recovery of Completely Denervated Muscle: Implications for Innervation of Tissue-Engineered Muscle

Abstract: Tissue-engineered muscle has been proposed as a solution to repair volumetric muscle defects and to restore muscle function. To achieve functional recovery, engineered muscle tissue requires integration of the host nerve. In this study, we investigated whether denervated muscle, which is analogous to tissue-engineered muscle tissue, can be reinnervated and can recover muscle function using an in vivo model of denervation followed by neurotization. The outcomes of this investigation may provide insights on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…33 Of particular interest is the innervation and formation of neuromuscular junctions, an obstacle to tissue engineering strategies for muscle repair, and a critical step for contractile control of engineered muscle graft tissue. 34 Our immunohistochemical stains show numerous nerve fibers branching from the grafted nerve into our engineered muscle, with individual nerve branches extending throughout the grafted region and terminating at clusters of acetylcholine receptors, demonstrating the in vivo development of neuromuscular junctions within the SMUs.…”
Section: Figmentioning
confidence: 63%
See 1 more Smart Citation
“…33 Of particular interest is the innervation and formation of neuromuscular junctions, an obstacle to tissue engineering strategies for muscle repair, and a critical step for contractile control of engineered muscle graft tissue. 34 Our immunohistochemical stains show numerous nerve fibers branching from the grafted nerve into our engineered muscle, with individual nerve branches extending throughout the grafted region and terminating at clusters of acetylcholine receptors, demonstrating the in vivo development of neuromuscular junctions within the SMUs.…”
Section: Figmentioning
confidence: 63%
“…34 Past studies in our lab have also demonstrated that reinnervation of the rat medial gastrocnemius muscle after denervation is an extensive process that may require over 3 months before maximum recovery is achieved. 35 Thus, despite the promising innervation and neuromuscular junction formation observed in our SMUs, it is likely that their neuromuscular interfaces had not yet fully matured after only 28 days in vivo.…”
Section: Figmentioning
confidence: 95%
“…36 Investigators have also begun to explore how such tissues can be re-enervated, for example in skeletal muscle preparations, guiding both vascular health as well as neural connectivity to the host. 37 These and other publications support the growing interest and increasing complexity in organ/native ECMbased tissue replacement approaches.…”
Section: Fisher and Mauckmentioning
confidence: 58%
“…The formation of NMJs and improved force generation have been reported for engineered muscles that were implanted around a femoral nerve (123), and motor function in denervated muscle has been recovered through transplantation of a peroneal nerve (124) or stem cell–derived motor neurons (125). Although in vitro coculture of engineered rodent muscle and motor neurons can yield the formation of functional NMJs and enhance force production (7476, 126), it is not clear that composite muscle–nerve constructs, although more complicated to produce, would add any benefit in vivo compared with the use of muscle-only constructs.…”
Section: Bioengineering Methods For Skeletal Muscle Research and Rmentioning
confidence: 99%